Peer to Peer Lending , E-Money, and Crowdfunding Economic Perspective Sharia - Novita Sari Pulungan; Andri Soemitra; Rukiah Lubis (Pusat Riset dan Inovasi Nasional, 2023)
The development of information technology has penetrated all financial sectors, including sharia financial technology. The concept of Sharia Fintech Innovation must be guided by the Qur'an and Sunnah. By the Fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI). Of the many startups registered with the OJK and BI, only a small number operate according to sharia principles. The lack of literacy related to sharia fintech innovation is the reason why conventional fintech products and services are more attractive to the public. This study aims to explain the concept of fintech products and services in sharia principles and is limited to three products, namely Peer to Peer Lending, E-Money, and Crowdfunding. The method used in this research is literature study, by taking various references and literature related to research. The results of the study explain that 1) Sharia principles related to peer-to-peer lending, e-money, and crowdfunding are by the Fatwa of the National Sharia Council-Indonesian Ulema Council, namely that one must avoid Riba, Gharar, Maysir , Tazlis, Ishraf and transactions of illicit goods. 2) The contracts used for peer-to-peer lending are in line with the characteristics of financing services such as al-bai', ijarah, mudharabah, musyarakah, wakalah bi al ujrah, and qardh. Whereas e-money uses two contracts, namely the contract between the Issuer and the Holder using a wadiah contract and the contract between publishers and traders using a wakalah contract.